2011
DOI: 10.1007/s11434-011-4563-3
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and molecular epidemiology of foot-and-mouth disease virus in China

Abstract: Foot-and-mouth disease (FMD), caused by foot-and-mouth disease virus (FMDV), is considered one of the most important viral diseases of cloven-hoofed animals, causing severe economic losses in affected regions of the world. Three serotypes (A, O, and Asia 1) of FMDV have been identified in China since 1958. In addition, the occurrence of novel subtypes within these serotypes has made the epidemiology of FMDV more complicated over the last few years. In this review, we summarize the history and the current epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Biochemistry Analyzer AU640 and Microscope BX50 were from Olympus Optical Co., Ltd., total bilirubin (TB), aspartate aminotransferase (AST), alanine aminotransferase (ALT) and plasma alkaline phosphatase (ALP) kit were from Nanjing Jiancheng Bioengineering Institute, China. DAOA, OA and ODA were isolated from E. adenophorum leaves, and purified (98 % purity) by the HPLC by our group [ 26 ]. Male and Female Kunming mice (SPF level), weighing from 20 to 24 g were obtained from Central Pharmacy (Experimental Animal Center of Shandong University, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemistry Analyzer AU640 and Microscope BX50 were from Olympus Optical Co., Ltd., total bilirubin (TB), aspartate aminotransferase (AST), alanine aminotransferase (ALT) and plasma alkaline phosphatase (ALP) kit were from Nanjing Jiancheng Bioengineering Institute, China. DAOA, OA and ODA were isolated from E. adenophorum leaves, and purified (98 % purity) by the HPLC by our group [ 26 ]. Male and Female Kunming mice (SPF level), weighing from 20 to 24 g were obtained from Central Pharmacy (Experimental Animal Center of Shandong University, China).…”
Section: Methodsmentioning
confidence: 99%
“…The main differences between DAOA and OA on molecular structure are the 2-acetoxy and 2-carbonyl groups, distinguishing feature between ODA and OA is the presence or absence of an unsaturation 6–11 bond in conjugation with a 7-oxo function. Our previous studies have reported the extraction and separation methods of sesquiterpenes, and demonstrated that DAOA, OA and ODA were mainly distributed in Ea leaves with 0.63–1.99 % of mass percentage in dry leaves [ 26 ]. If these sesquiterpenes could find application in biology medical or biopesticides fields, Ea will have greater development value.…”
Section: Introductionmentioning
confidence: 99%
“…This peptide immunogen induced neutralising antibodies in mice against FMDV O/Mya/98, the strain responsible for the prevalence of FMD in Mainland China in 2010, as well as antibodies against the O/HN/93 vaccine strain. These two isolates belong to the Southeast Asia and Cathay topotypes of type-O FMDV (Bai et al, 2011). The results of the present study indicated that current approach is effective for these two topotypes of O-type FMDV; however, it is still necessary to evaluate the effectiveness on a wider range of O-type FMDVs.…”
Section: Discussionmentioning
confidence: 69%
“…In China, FMD was first reported in 1958 ( Bai et al, 2011 ). In that same year, serotypes O and A isolates were collected from the Xinjiang Uygur Autonomous Region ( Bai et al, 2009 ; Li et al, 2007 ) and serotype Asia 1 isolate was collected from Yunnan province ( Du et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%